The Implementation of Image Media on Arabic Speaking Skills Case Study Class VIII Mts Jidris Assalam Purbaratu Tasikmalaya City - Machmud Yunus; Pira Lia Nurfajar (al-Afkar, Journal For Islamic Studies, 2023)
The title of this research is "The Implementation of Image Media on Arabic Speaking Skills at MTs Jidris Assalam Purbaratu." Learning media support the success of a teaching and learning activity, and one of them is image media. Picture media is expected to be one of the effective media for students to hone Arabic speaking skills. Because what is expected from learning a language is speaking skills. This study aims to determine the implementation of image media on Arabic speaking skills at Mts Jidris Assalam Purbaratu. Qualitative methods are used to obtain information through classroom action and data collection through observation, interviews, and documentation. The results of the implementation of image media on Arabic speaking skills were carried out but not optimally due to inadequate facilities and infrastructure.